2017
DOI: 10.3329/pa.v27i4.32120
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous proline enhances nutrient uptake and confers tolerance to salt stress in maize (Zea mays L.)

Abstract: Proline accumulation is the main adaptive mechanism to salinity in plants. The pot experiments were carried out to mitigate the adverse effects of NaCl stress on BARI Hybrid Maize-5 and Hybrid Maize Pacific-987 by exogenous application of proline. Plants were exposed to different concentrations of NaCl at vegetative stage. Proline solutions were sprayed over maize leaves at both vegetative and tasseling stages. NaCl stress caused significant reductions in plant growth of maize. NaCl stress at 50 mM drastically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…It's clear from the data that application of nitrogen fertilization levels increased N, P, K % and proline content in absence or presence of proline, and found that, highest values observed with application of 150% N+50 ppm proline. This may be owed to the effective role of nitrogen in availability of nutrient in soil then its absorption by roots Similar results were obtained by Hafez and Abdelaal 2015;Woldesenbet andHaileyesus 2016 andAnjum 2017).Thus, application of exogenous proline could be an efficient means of decrease the adverse effects of irrigation interval on plants as has been observed in the present study (Alam et al 2016 andBaddour et al, 2017).…”
Section: Chlorophyll Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…It's clear from the data that application of nitrogen fertilization levels increased N, P, K % and proline content in absence or presence of proline, and found that, highest values observed with application of 150% N+50 ppm proline. This may be owed to the effective role of nitrogen in availability of nutrient in soil then its absorption by roots Similar results were obtained by Hafez and Abdelaal 2015;Woldesenbet andHaileyesus 2016 andAnjum 2017).Thus, application of exogenous proline could be an efficient means of decrease the adverse effects of irrigation interval on plants as has been observed in the present study (Alam et al 2016 andBaddour et al, 2017).…”
Section: Chlorophyll Contentsupporting
confidence: 90%
“…These results are in accordance with (Hafez and Abdelaal 2015;Woldesenbet andHaileyesus 2016 andAnjum 2017). With some help from foliar application of proline to avoid stress by irrigation interval These results are similar to the findings of (Alam et al 2016;Al-Shaheen and Soh 2016).…”
Section: Yield Attributedsupporting
confidence: 88%
“…Exogenous proline increased fresh and dry biomasses, grain yield and 1000-grain weight of salt-stressed T. aestivum (Rady et al, 2019). In salt-stressed Z. mays, foliar-applied proline increased the number of seeds per plant, total grain weight and the 100-grain weight (Alam et al, 2016). In general, exogenous application of proline increased plant growth and productivity under salt-induced stress but the underlying mechanisms, probably linked to some hormonal regulation, still remain elusive.…”
Section: Effects Of Proline Treatment On Plant Growth and Biomass Undmentioning
confidence: 97%
“…This capability can be improved and enhanced by the use of amino acids under salt stress (Wang et al, 2010). For example, exogenous applications of amino acids has been reported to reduce abiotic stresses in various crop species such as wheat (El-Said and Mahdy, 2016), maize (Alam et al, 2017), rice (Xiaochuang et al, 2017), barley (Genisel et al, 2015), potato (Awad et al, 2007), faba bean (Sadak et al, 2015), Arabidopsis thaliana (Dominguez-Solis et al, 2004) and canola (Lei et al, 2016) etc.. About 80% human food is derived from crops in which only cereals (wheat, rice and maize) contribute 50% of total food production throughout the world (Langridge and Fleury, 2011). However, major food crops are deficient in vital amino acids such as lysine plus tryptophan in cereals (Pfefferle et al, 2003), isoleucine, cysteine and methionine in potatos (Stiller et al, 2007), and threonin and methionine in soybeans (Muntz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, exogenous application of amino acids regulate antioxidant defense system in soybean when applied in combination at very low concentration e.g., alanine, glutamate, cysteine and glycine (Teixeira et al, 2017). Alam et al (2017) reported that amino acids maintain nutrients balance in maize hybrids under salt stress. Some amino acids such as serine, glycine, valine and glutamate play role in improving plant health through therapeutic elements (Moran-Palacio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%